LIFE TABLE AND LIFE CYCLE GRAPHIUMEVEMON (LEPIDOPTERA: PAPILIONIDAE) ON SOURSOP (ANNONA MURICATAL.) - MIMI HALIMAH; YAYAN SANJAYA; NIA NURDIANI; CITA TRESNAWATI (Sriwijaya University Learning and Education International Conference, 2016)
Butterflies choose one or several particular plant species which are very closely as a place of food and life, as well asG. evemon. Soursop plant(Annona nuricata) is one of the natural food for the G.evemoncaterpillars. This plant is widely spread both along the highway and in the office complex.Until now there is no research on the life cycle and life table of theG.evemon in the soursopplant. However the need of this information is important to preserve the existence of a butterfly as one of pollinating insects to determine the biotic potential of the G. evemon.The purposes of this study are to determine the life cycle andmorphometric of G.evemon. This study uses rearing method and the subject of the study are 30 eggs G. evemon.The length of time and morphology of each pre-adult stages ofthe G.evemon was recorded. The calculations in the table are based on the life stage of the development and mortality of each stage of the development of G. evemon.The results showed that the average time of the G.evemonlife cycle onsoursop plant was 28 – 50days. The morphology of each stage has a specific characteristic.